2010
DOI: 10.3892/ol_00000014
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre phase II study of leucovorin plus pharmacokinetic modulating chemotherapy for metastatic colorectal cancer

Abstract: Abstract. The optimal administration of 5-fluorouracil (5-FU)/leucovorin (LV) for colorectal cancer (CRC) has yet to be fully defined although evidence of the combination has already been established. In a multicentre phase II study, pharmacokinetic modulating chemotherapy (PMC), which is based on the concept that continuous intravenous 5-FU infusion can be enhanced by low-dose oral uracil/tegafur, was combined with LV and administered. Thirty-seven patients were enrolled. The objective response rate was 31.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In particular, recent reports suggested that the pharmacokinetics of 5-FU remain an important factor that affects the prognosis of patients with CRC, even after the introduction of modern chemotherapy for CRC [7477]. An implantable port system is indispensable in both HAI and central venous port systems to optimize the pharmacokinetics in multiagent chemotherapy.…”
Section: Importance Of Pharmacokinetics In the Chemotherapy For Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent reports suggested that the pharmacokinetics of 5-FU remain an important factor that affects the prognosis of patients with CRC, even after the introduction of modern chemotherapy for CRC [7477]. An implantable port system is indispensable in both HAI and central venous port systems to optimize the pharmacokinetics in multiagent chemotherapy.…”
Section: Importance Of Pharmacokinetics In the Chemotherapy For Crcmentioning
confidence: 99%
“…Even in modern chemotherapy using several active agents, 5-FU plays a central role in the treatment of CRC, and many attempts have been made to improve its efficacy and potentiate its action over the last 50 years. In particular, recent reports suggested that the pharmacokinetics of 5-FU remain an important factor that affects the prognosis of patients with CRC, even after the introduction of modern chemotherapy for CRC [ 74 77 ]. An implantable port system is indispensable in both HAI and central venous port systems to optimize the pharmacokinetics in multiagent chemotherapy.…”
Section: Importance Of Pharmacokinetics In the Chemotherapy For Crcmentioning
confidence: 99%